2013
DOI: 10.3389/fphys.2013.00087
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive impairment in childhood chronic fatigue syndrome

Abstract: Neurocognitive impairment is a feature of childhood chronic fatigue syndrome (CCFS). Several studies have demonstrated reduced attention control in CCFS patients in switching and divided attention tasks. In students, the extent of deterioration in task performance depends on the level of fatigue. Poor performance in switching and divided attention is common in both fatigued students and CCFS patients. Additionally, attentional functions show dramatic development from childhood to adolescence, suggesting that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
5
0
1
Order By: Relevance
“…This suggests that the brain may require increased recruitment (cognitive compensation) to compensate for poorer task performance. 71 Some of the abnormalities improved as children’s fatigue improved after CBT; however, this is only one small study and the results need to be replicated. 71 General strategies to help children with attention difficulties may be helpful and include attention process training, working on the school environment to help children maintain attention, as well as strategies to improve memory, including overviews, slowing the pace of new information, and providing verbal information with visual prompts.…”
Section: Epidemiologymentioning
confidence: 93%
“…This suggests that the brain may require increased recruitment (cognitive compensation) to compensate for poorer task performance. 71 Some of the abnormalities improved as children’s fatigue improved after CBT; however, this is only one small study and the results need to be replicated. 71 General strategies to help children with attention difficulties may be helpful and include attention process training, working on the school environment to help children maintain attention, as well as strategies to improve memory, including overviews, slowing the pace of new information, and providing verbal information with visual prompts.…”
Section: Epidemiologymentioning
confidence: 93%
“…Fatigue induces difficulty in initiating or sustaining voluntary activities ( Chaudhuri and Behan, 2004 ). In fact, fatigued children and adolescents and patients with childhood chronic fatigue syndrome (CCFS), which is characterized by profound and disabling fatigue for 6 months ( Fukuda et al, 1994 ), show poor performance on cognitive tasks related to memory and attention ( Haig-Ferguson et al, 2009 ; Kawatani et al, 2011 ; Mizuno et al, 2013a ; Tomoda et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since previous studies have revealed that a switching attention task is useful for evaluating reduced performance under fatigue conditions, 43 44 45 we used task E of the modified advanced trail making test (mATMT) as a switching attention task for evaluating executive function. 46 47 Circles with numbers (from 1 to 13) or kana (Japanese phonograms, 12 different letters) were shown in random locations on a screen, and participants were required to use a computer mouse to alternately touch the numbers and kana; this task thus required switching attention.…”
Section: S Ubjects and M Ethodsmentioning
confidence: 99%